BOF process dynamics. Issue 1 (3rd April 2019) - Snigdha, Ghosh; Bharath, Ballal N.; Viswanathan, Nurni N.
ABSTRACT: The Basic Oxygen Furnace (BOF) process is an exceedingly fast refining process needing a good dynamic model for better understanding and dynamic control. The process is characterised by reactions at multiple scales: at the scale of the metal bath and the slag and at the scales of droplets and bubbles. The reactions take place at multiple sites too. The presence of the supersonic jet interacting with the metal bath and the slag layer, producing various sizes of drops in the emulsion which on reaction produce copious bubbles at its interface, lime dissolution issues, etc., make the description of the dynamics of the process complex and fascinating. There are still areas where an adequate quantitative description needs further research.